Rekomendasi Desain Mebel Sebagai Pendukung Identitas Visual Brand : Studi Kasus: Brand Vespa Piaggio - Mohd Ridho Kurniawan; Delsa Rezna Junita (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The application of visual brand concepts in showroom interior planning is considered crucial to ensuring that the products offered are relevant to the target market. This study aims to design a concept for the cash register and backdrop facilities in the case study of the Vespa Piaggio brand, with the goal of effectively reflecting the brand's visual identity. This research employs a qualitative method through in-depth observation, including direct visits to Piaggio stores and documentation via photographs and videos. The findings indicate that the use of shape metaphors aligned with the brand's identity can strengthen the visual brand image and enhance the showroom's appeal. The implications of this study emphasize the importance of applying visual identity holistically in furniture design to build a positiveerception among the target market and potential customers.